1936
DOI: 10.1042/bj0300692
|View full text |Cite
|
Sign up to set email alerts
|

Hexosephosphates produced by higher plants

Abstract: THE fact that phosphates stimulate the respiratory sugar metabolism in higher plants suggests that the formation of phosphoric esters may occur as part of this process. Stoklasa et al. [1904-1913] obtained cell-free zymase-like preparations from peas, beetroots , potatoes etc., which actively fermented sugars. Bodnar [1916] confirmed these results under strictly aseptic conditions, since some investigators had attributed Stoklasa's findings to bacterial contamination. Evidence of phosphorylation was first give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1943
1943
1961
1961

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…One of these might be phosphoric acid and its esters, particularly the hexosephosphates. There is considerable evidence that these esters are present in plant tissues (4,15,21,40,41). In view of the recent work with phosphorylation in plant tissue extracts and intact plant organs (see STAUFFER, 39) it appears probable that during changes in carbohydrate content there may be changes in the relative amounts of various phosphate esters and their salts.…”
Section: Methodsmentioning
confidence: 99%
“…One of these might be phosphoric acid and its esters, particularly the hexosephosphates. There is considerable evidence that these esters are present in plant tissues (4,15,21,40,41). In view of the recent work with phosphorylation in plant tissue extracts and intact plant organs (see STAUFFER, 39) it appears probable that during changes in carbohydrate content there may be changes in the relative amounts of various phosphate esters and their salts.…”
Section: Methodsmentioning
confidence: 99%
“…A mixture of the two esters was isolated by Robison from yeast and by Embden from muscle; these esters are also known to occur in higher plants (19). A phosphohexoisomerase capable of catalyzing the reversible interconversion of glucose-6-phosphate to fructose-6-phosphate and man nose-6-phosphate, was shown by Tank6 (20) to exist in pea extracts. Somers & Cosby (21) also found that fructose-6-phosphate is converted by pea seed extracts into an aldose monophosphate, presumed to be glucose-6-phosphate.…”
Section: Bassid and Putmanmentioning
confidence: 98%
“…Pea meal has been a favorite material and, under appropriate conditions, accumulates glucose 1-phosphate in considerable quantities (76). Alternatively, fructose 1,Bdiphosphate and mixed hexose &phosphates have been isolated (76,191). Sedoheptulose phosphate has been identified in spinach leaf preparations fed with ribose 5-phosphate (10).…”
Section: (1) Phosphate Ester8mentioning
confidence: 99%